DESIGN OF POWER MANAGEMENT SUBSYSTEM ON WATER QUALITY MONITORING SYSTEM FOR FLOATING NET CAGES - Albertha, Felicia
The water quality monitoring system in the floating net cage is located in a reservoir, so it cannot receive power directly from the electric grid. Therefore, a power management subsystem is needed to provide resources and manage all system power requirements efficiently. The resource used is an alternative energy source (solar energy). The solar cell will detect the sunlight and convert it into electricity and then charge the battery. The battery will supply power to meet the needs of the whole system. This system does not have to be active all the time because the water conditions in the reservoir tend not to fluctuate, so the system sets to be active only every 30 minutes. This period will be set using an external timer circuit using the astable mode IC555 which has an off-time of 28 minutes and an on-time of 2 minutes to retrieve water quality information. This timer is also used to optimize and save system power consumption significantly compared to the sleep mode on the microcontroller. The main components of this subsystem are polycrystalline solar panels (chosen because have more resistant to weather changes) 6V 6W, and Lithium-Ion rechargeable batteries (chosen because having a larger electrical capacity, easier to obtain and maintain) installed in two series and two parallel. When combined with the overall system, this subsystem functionality can work properly. The system can remain active when it does not receive sunlight, battery charging can occur using a solar panel or micro USB for extreme conditions, the on/off timer period is appropriate, and battery durability (in testing, the system lasted three days in a row). From the results, this subsystem has also answered several related specifications, i.e., having a power consumption of 1909.63 mW, a working voltage of 5V, a battery capacity of 16000 mAh, a data transmission period of 30 minutes ± 2 minutes, and charging using energy harvesting